2014
DOI: 10.1007/s13105-014-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine ameliorates imbalance of redox homeostasis and inflammation in an acute kidney injury model

Abstract: Ischemia-reperfusion (IR) has been reported to be associated with augmented reactive oxygen radicals and cytokines. Currently, we aimed to examine the influence of fluoxetine, which is already used as a preoperative anxiolytic, in the context of IR induced by occlusion of infrarenal abdominal aorta (60 min of ischemia) and its effects on renal oxidative status, inflammation, renal function, and cellular integrity in reperfusion (120 min post-ischemia). Male rats were randomly assigned as control, IR, and pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…TNF-α was also reported as an upstream regulator for MMP-9 [43]. In our study, we found that fluoxetine downregulated these inflammatory cytokines, which is in accordance with previous studies [44, 45]. TLRs belong to a large family of pattern recognition receptors that play a key role in innate immunity and inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…TNF-α was also reported as an upstream regulator for MMP-9 [43]. In our study, we found that fluoxetine downregulated these inflammatory cytokines, which is in accordance with previous studies [44, 45]. TLRs belong to a large family of pattern recognition receptors that play a key role in innate immunity and inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…First, the activation of TNF-α, IL-1β and IL-6 could promote the synthesis of leukocytes and release superoxide and proteolytic enzymes to result in loss of cellular integrity [35]. On the other hand, increased ECM expression induced by IL-6 in turn result in glomerular hypertrophy and narrowing renal tubular lumen [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of depression cannot be considered to be responsible for this observation. The second possibility suggests the pleiotropic anti‐inflammatory, 22,41 antioxidative, 42 and anticollegenolytic 22 properties of fluoxetine contributing toward better periodontal health in patients receiving this medication. This explanation seems credible in light of the demonstration of downregulation of the matrix metalloproteinase (MMP) level by fluoxetine in the studies by Li et al, 21 Benekareddy et al, 43 and Branco‐de‐Almeida 22 .…”
Section: Discussionmentioning
confidence: 99%